Peru : Staying the Course of Economic Success - Werner, Alejandro; Santos, Alejandro (Washington, D.C. : International Monetary Fund, 2015)
Peru stands out among Latin American countries as an example of successful economic reforms over the past decade. This comprehensive look at Peru's economy traces that country's journey from a debt crisis in the 1980s to having buffers in place that allowed it to emerge unscathed from the global financial crisis. The book examines the steps Peru undertook to achieve these results and extracts lessons to be learned. Chapters are written by IMF staff and Peruvian economists.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet